Comparing adolescent and adult substance users in terms of hiv/aids knowledge - Erdoğan, Funda Nazlı; Ögel, Kültegin; Devletkuşu, Canan (Journal of Dependence, 2009)
Objective: The objective of the research is to compare adolescent and adult substance users in terms of the HIV/ AIDS knowledge.Method: Between August 2006- June 2007, a halfstructured questionnaire filled by the adolescent and adult substance users who are staying at the care centers of Social Services, detention centers and addiction treatment cliniques.Results: The sample consist of 489 adolescent and adult substance users in Social Services, prisons and substance treatment centers. In the whole sample the girls' mean number of the correctly answered questions were higher than boys' scores. The participants who have high school and upper education has higher mean number of the correctly answered questions than the secondary and lower education. In different age groups, there weren't any significant diffrence in term of the mean number of the correctly answered questions.Conclusions: By taking all the results into account, during the constitution of HIV/AIDS prevention programs, especially the needs of low educated, male adolescents, under the age of 21 should be considered.
Keywords: Age; HIV/AIDS knowledge; addiction; substance user